Decisional Dignity: Teenage Abortion, Bypass Hearings, and the Misuse of Law - Sanger, Carol (Columbia Journal of Gender and Law, 2009)
How might we think about reforming abortion regulation in a world in which the basic legality of abortion may, as a matter of constitutional law, at last be relatively secure? I have in mind the era just upon us in which the overturn of Roe v. Wade1 no longer looms so threateningly over the reproductive rights community in the United States and is no longer necessarily its central concern. There is now a general and seemingly well- founded optimism that under the Obama administration, those who support and rely on reproductive rights will not have to pray nightly for the health of Supreme Court justices (although we wish them well). As Senator Obama said in 2008 on the 35th anniversary of Roe: “With one more vacancy on the Supreme Court, we could be looking at a majority hostile to a woman’s fundamental right to choose for the first time since Roe v. Wade. The next president may be asked to nominate that Supreme Court justice. That is what is at stake in this election.” It appears that since January 20, 2009, Justice Stevens may, if he wishes, hang out rather than hang on, and the rest of us may now be more confident that vacancies on the court are less likely to put the basic right to abortion in jeopardy. President Obama’s first Supreme Court appointment, Sonia Sotomayor, characterized the Court’s decision in Planned Parenthood vs. Casey as “settled” and “the precedent of the court” during her confirmation hearings. While confidence in a justice’s future decisions is never assured, it seems, for the moment anyway, that Roe will not be overturned.